Comparative Trapping Efficiency to Characterize Bee Abundance, Diversity, and Community Composition in Apple Orchards - Joshi, N.K.; Leslie, Timothy; Rajotte, Edwin G.; Kammerer, Melaine A.; Otieno, Mark; Biddinger, David J. (Oxford University Press, 2015)
Bees are important pollinators of numerous crops, and monitoring their abundance and diversity in commercial agricultural ecosystems is of increasing importance due to pollinator declines. In season-long field studies conducted in Pennsylvania during 2011–2013, we evaluated five different bee monitoring passive traps—three pan traps (blue, yellow, and white) and two vane traps (blue and yellow)—for their effectiveness and utility for monitoring bees in commercial apple orchards. Traps were placed prebloom and were monitored weekly until the end of crop season (mid-October). We recorded 14,770 bees comprising 118 species, 27 genera, and five families. The most abundant species were Augochlora pura (Say) (34.4% of total), Ceratina calcarata Robertson (15.5%), Bombus vagans Smith (7.8%), Bombus impatiens Cresson (6.4%), and Apis mellifera L. (4.3%). Bee abundance was highly variable among trap types across the three years and during the bloom and postbloom period. Blue vane traps were found to be the most effective trap type, with significantly higher rates of per-sample species accumulation than all other traps. Species richness estimates were highest for the blue vane and blue pan traps. This study reveals the utility and effectiveness of various traps for studying abundance and diversity of pollinator bees in commercially managed apple orchards. It also provides baseline information about the bee community found during the bloom and postbloom periods in Pennsylvania apple orchards that can be used to measure changes in bee community structure and abundance due to conservation efforts, such as reduced risk IPM programs, habitat management, and augmentation.
DOI: http://dx.doi.org/10.1093/aesa/sav057
Keywords: bee; pollinator; monitoring; pan trap; vane trap